Economic Evaluation of Waste Management in Luangprabang Capital Case Study Group of Ban WatThat - XIONGTOUA, Tongvang; CHANTHAVONE, Thongphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The paper explores the economic evaluation of waste management in Luangprabang, Case study “Group of Vatthad villagers”, conducted questionnaires to ask 292 families. Which is 159 responders are males and other 133 are females. The results of study show that: The 234 householders, covering 80,13% are willingness to pay and while others are not willingness to pay. For the estimation results using the Logit Model found that older respondents were more willingness to pay for waste management than younger with the significance level of 0.1. The reason for that is the older people care more about the environment. In terms of paying the fee, male are more willingness to pay than female with the significance level of 0.1. The reason for that is men are more engaged in social events which result in feeling more environment care. The households who run business at home are more willingness to pay the fee than others who do not run business at their own home with the confidence level of 99%. Obviously, the business place like a house discards more waste than the normal houses. In terms of the fee price and the willingness to pay, there are related in opposite with the significance level of 0.01. It turns out that the higher fee price makes villager willingness to pay lesser and wise versa. The personal education, status, occupation and income of the responders have no impact on the willingness to pay because, the hypothesis testing, there are accepted null hypothesis. Economic evaluation of waste management of Vatthad villagers in the condition of applying average willingness to pay per month is 31,166.69 kip, the results shows that total economic values is 33,971,698.41 kip per month and 407,660,272.86 kip per year.